WIRE BREAKAGE DURING WIRE DRAWING DUE TO THE PRESENCE OF SURFACE DEFECTS, INHERITED FROM WIRE ROD - A. S. Siarohina (Литьë и металлургия)
The main causes of wire breakage during drawing are listed, the appearance signs and peculiarities of metallographic structure of destruction are described. The type and cause of the breakage could be identified on basis of this description. The transformation of defects in the drawing process is presented.